Dominant Factors Affecting Stress Levels Among Emergency Room Nurses at Waled Hospital - Hasril Desiathul Hamdani (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: This study aims to identify the dominant factors influencing the stress levels of emergency room nurses at Waled Hospital. Method: The research design used was quantitative with a descriptive correlational design and a cross-sectional approach. A total sampling technique was used, involving 55 respondents. The instrument utilized was a validated questionnaire, and data were analyzed using Spearman rank correlation. Result: Results showed that the majority of nurses had high stress levels and that workload, fear of infection, and inadequate personal protective equipment were the dominant stress factors (p = 0.004; r = -0.289). Conclusion: It is concluded that stress levels among ER nurses are significantly affected by these dominant factors. Comprehensive stress management strategies are recommended to reduce psychological burden and maintain quality of care.